Development of directed global inhibition, competitive inhibition and behavioural inhibition during the transition between infancy and toddlerhood. Issue 5 (7th December 2021) - Hendry, Alexandra; Greenhalgh, Isobel; Bailey, Rhiannon; Fiske, Abigail; Dvergsdal, Henrik; Holmboe, Karla
Abstract: Inhibitory control (IC) is a core executive function integral to self‐regulation and cognitive control, yet is itself multi‐componential. Directed global inhibition entails stopping an action on demand. Competitive inhibition is engaged when an alternative response must also be produced. Related, but not an executive function, is temperamentally‐driven wariness of novelty, known as behavioural inhibition. Understanding early development of these components has been hampered by a shortage of suitable measures. We combine established and novel measures to capture directed global inhibition (Toy Prohibition, Touchscreen Prohibition), competitive inhibition (A‐not‐B, Early Childhood Inhibitory Touchscreen Task; ECITT) and behavioural inhibition (Touchscreen Approach) in 113 10‐ and 16‐month‐olds (73 seen longitudinally). ECITT performance shows good 1‐week test‐retest reliability at 10‐months ( r  = 0.30–0.60) but little stability to 16‐months. Directed global inhibition performance shows developmental progression but little stability of individual differences from 10 to 16 months. Performance on measures targeting similar IC components shows greater coherence at 16‐months ( r  = 0.23–0.59) compared with 10‐months ( r  = 0.09–0.35). Probing of ECITT condition effects indicates toddlers are more able, compared with infants, to override immediate prepotencies; indicative of increasingly flexible control over behaviour. However, exerting IC over cumulative prepotencies appears just as challenging for toddlers as infants. Exploratory analyses show little evidence for cross‐sectional or longitudinal associations between behavioural, directed global and competitive inhibition. In combination, these findings indicate that IC is not yet a stable, unidimensional construct during the transition between infancy and toddlerhood, and highlight the need for careful selection of multiple measures for those interested in capturing early variation in IC.